A influência da confiabilidade e relevância da informação contábil sobre o desempenho das companhias de capital aberto - Frank Nero Pena de Vasconcelos (2014)
The investors by not having the same level of information those managers need tools capable of providing conditions for assessing the situation of the company. In this context, accounting assumes a position of prominence by disclosing accounting information. Though, it is expected that this information have a high degree of quality, ie, the information must have properties in order to ensure its utility, here called the qualitative characteristics of information so that investors can get better conditions to allocate their resources. Therefore, this research aimed analyze the influence of the qualitative characteristics of accounting information "reliability and relevance" on the performance of Brazilian companies publicly traded in the period 2008-2012. For this, were analyzed 70 listed companies in BM&FBOVESPA and composing IBrX index. Because it is an analysis that involves dimensions of cross section and time series, the methodology used was the analysis of panel data. In relation the variable of interest qualitative characteristics of accounting information reliability and relevance it was used the model proposed by Jonas and Blanchet (2000), Gabriel (2011) and Braam and Beest (2013) to assist in the establishment of an index. As a proxy for performance of the firm, it was used the Index Return on Assets (ROA) and Firm Value (FV), as directed by Canonical Correlation. At the model performance estimated by variable ROA, the best model was the Random Effects, and model performance estimated by variable VF, the prevailing model of Fixed Effects. However, was found the presence of serial autocorrelation and heteroscedasticity in both, which forced to use the model Feasible Generalized Least Squares (FGLS). The results in both models allowed reply the question formulated research, demonstrating that there is statistical evidence that treated both the model performance based on a financial ratio, as in the model which was based on market value, had a positive and statistically significant relationship with the variable qualitative characteristics of accounting information reliability and relevance.